Molecular Phylogenetics and Biological Potential of Fungal Endophytes From Plants of the Sundarbans Mangrove - Rahaman, Md Sohanur; Siraj, Md Afjalus; Sultana, Sabiha; Seidel, Veronique; Islam, Md Amirul (Frontiers in Microbiology, 2020)
The Sundarbans forest in Bangladesh is the world’s largest mangrove. It is a unique ecosystem where living organisms face extreme challenges to compete for survival. Such competition results in the production of bioactive molecules which are useful for agriculture and human health. In this study, eighty fungal endophytes from nine mangrove plants growing in a region, as yet unexplored, of the Sundarbans were isolated by surface sterilisation and pure culture techniques. Among the eighty isolates subjected to a preliminary antimicrobial screening using an agar plug diffusion assay, only fifteen showed some promising activity. These were subsequently identified by polymerase chain reaction of their ITS gene. Extracts prepared from the identified isolates were screened for antimicrobial, antioxidant, cytotoxic and α-glucosidase inhibitory activities. Their total polyphenol and flavonoid content and their FRAP value were also determined. All endophytes are reported for the first time in the plants under investigation.